Echocardiographic Findings of ICU-Admitted COVID-19 Patients: a Multicenter Retrospective Study - Hossein Hatami; Mohammad Ali Akbarzadeh; Latif Gachkar; Amirreza Keyvanfar (Novelty in Biomedicine, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has left many victims and caused many problems for the healthcare systems of different countries. Many COVID-19 patients have cardiovascular complications, which are detectable using echocardiography. This study aimed to determine the echocardiographic findings and their association with mortality in an intensive care unit (ICU)-admitted COVID-19 patients.